Application Learning Model Cooperative Script for Increasing Listening Skills in the Elementary School Students - Vira Dahnia; Yenni Fitra Surya; M Syahrul Rizal; Putri Hana Pebriana; Fadhilaturrahmi Fadhilaturrahmi (Universitas Muhammadiyah Enrekang, 2022)
This study aims to improve students' listening skills through the cooperative script model for fifth grade students at SDN 008 Langgini in the 2022/2023 academic year. The type of research used is Classroom Action Research. This research consisted of 2 cycles and each cycle was conducted in 2 meetings. The object of research is students' listening skills. Data analysis techniques were carried out in qualitative and quantitative descriptions. This research was conducted in 2 cycles, each cycle lasting 2 meetings. The results showed that students' listening skills improved after the action was taken. The results showed that the use of the cooperative script model could improve the listening skills of fifth grade students at SDN 008 Langgini. This is indicated by an increase in the number of students who achieve the minimum completeness criteria (KKM) and an increase in class and classical average scores. average value and percentage of classical completeness cycle I meeting I 40%, in cycle I meeting II 53.33 % and cycle II meeting I 80% in cycle II meeting II 93.33 % Keywords: Cooperative Script Learning Model, Listening Skills, and Elementary School.